How to identify the genetic basis of gastrointestinal and liver diseases?. (1st May 2003) - Ferenci, P
Abstract : New insights into the genetic basis of disease are being generated at an ever increasing rate. This explosion of information was ignited by technological advances, such as the polymerase chain reaction and automated DNA sequencing. Although its promise is great, the integration of genetics into the everyday practice of medicine remains challenging. This review discusses the application of molecular genetics in general with a specific focus on hereditary diseases of the digestive organs. The application of molecular genetics in everyday clinical routine is hampered by the difficult interpretation of test results. These difficulties include the prediction of disease penetrance, the presence of multiple mutations of a particular gene with varying functional consequences, and the importance of exogenous factors modulating disease expression. To date, the most significant impact of genetics has been to increase our understanding of disease aetiology and pathogenesis and to reliably identify siblings of affected patients with the risk to develop symptomatic disease.